Deletion of the polyketide synthase‐encoding gene pks1 prevents melanization in the extremophilic fungus Cryomyces antarcticus - Catanzaro, Ilaria; Gerrits, Ruben; Feldmann, Ines; Gorbushina, Anna A.; Onofri, Silvano; Schumacher, Julia (2024)
Cryomyces antarcticus , a melanized cryptoendolithic fungus endemic to Antarctica, can tolerate environmental conditions as severe as those in space. Particularly, its ability to withstand ionizing radiation has been attributed to the presence of thick and highly melanized cell walls, which—according to a previous investigation—may contain both 1,8‐dihydroxynaphthalene (DHN) and L‐3,4 dihydroxyphenylalanine (L‐DOPA) melanin. The genes putatively involved in the synthesis of DHN melanin were identified in the genome of C. antarcticus. Most important is capks1 encoding a non‐reducing polyketide synthase (PKS) and being the ortholog of the functionally characterized kppks1 from the rock‐inhabiting fungus Knufia petricola . The co‐expression of CaPKS1 or KpPKS1 with a 4′‐phosphopantetheinyl transferase in Saccharomyces cerevisiae resulted in the formation of a yellowish pigment, suggesting that CaPKS1 is the enzyme providing the precursor for DHN melanin. To dissect the composition and function of the melanin layer in the outer cell wall of C. antarcticus , non‐melanized mutants were generated by CRISPR/Cas9‐mediated genome editing. Notwithstanding its slow growth (up to months), three independent non‐melanized Δ capks1 mutants were obtained. The mutants exhibited growth similar to the wild type and a light pinkish pigmentation, which is presumably due to carotenoids. Interestingly, visible light had an adverse effect on growth of both melanized wild‐type and non‐melanized Δ capks1 strains. Further evidence that light can pass the melanized cell walls derives from a mutant expressing a H2B‐GFP fusion protein, which can be detected by fluorescence microscopy. In conclusion, the study reports on the first genetic manipulation of C. antarcticus , resulting in non‐melanized mutants and demonstrating that the melanin is rather of the DHN type. These mutants will allow to elucidate the relevance of melanization for surviving extreme conditions found in the natural habitat as well as in space.